La gestión del programa de entretenimiento deportivo general en el desarrollo de las cualidades físicas - Llanos Carranza, Angel (2017)
The present research work entitled “MANAGEMENT GENERAL SPORTS TRAINING PROGRAM IN THE DEVELOPMENT OF PHYSICAL QUALITIES IN FIRST YEAR STUDENTS OF PHYSICAL EDUCATION SPECIALTY , E.A.P.E.B. UNHEVAL - HUÁNUCO 2013” , aimed to test the degree of effectiveness of the management of General Athletic Training Program to develop the physical qualities: speed strength , endurance and flexibility in the students of the first year of the Specialty of Physical Education the , Academic Professional School of Basic Education , Faculty of Education UNHEVAL . In order to deepen the analysis and interpretation of the results as a method of experimental design was employed experimental Quasi subclass , we chose a single work group comprised of 18 students in the first year of the Specialty of Physical Education , applying pre test and post test , both expressed in the vigesimal system . For the statisticians estimate was used for descriptive statistics and contrasting the hypothesis test was applied distribution of “t” student. Results: Final analysis to rule out the null hypothesis and accept the alternative hypothesis, ie we have sufficient evidence to prove that the “Application for managing sports training program generally has high effectiveness in the development of students’ physical qualities the first year of the Specialty of Physical Education, Academic Professional School of Basic Education, UNHEVAL - Huánuco”. Conclusions: We have shown that the application of the management of sports training program generally significantly develops physical qualities of the students.